Pengaruh Pertumbuhan Penjualan, Strategi Bisnis, dan Intensitas Modal terhadap Penghindaran Pajak - Ria Savitri; Juli Ismanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of sales growth, business strategy, and capital intensity on tax avoidance in property & real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employed a quantitative approach with a descriptive method. The data used were secondary data obtained from company financial statements and analyzed using panel data regression with the assistance of EViews 12 software. The research sample was determined using a purposive sampling technique and consisted of 80 observations. The results showed that simultaneously sales growth, business strategy, and capital intensity significantly affected tax avoidance. Partially, sales growth and business strategy had no effect on tax avoidance, while capital intensity had a positive effect on tax avoidance. This study indicates that a higher level of investment in fixed assets can increase a company’s tendency to engage in tax avoidance through the utilization of depreciation expenses on fixed assets.